Kepastian Hukum atas Overlapping Penguasaan Tanah di Ibu Kota Nusantara (IKN) - Prayogo, Valencia; Olivia Cherie; Nayra Hanun (Fakultas Hukum Universitas Airlangga, 2025)
This research aims to analyze the overlapping issuance of land certificates in the IKN (New Capital City) on customary community land and the provision of inadequate compensation, which remains an unresolved issue. This research will discuss legal protection for overlapping in the issuance of land certificates for freehold owners and for holders. It will also examine the responsibility of the National Land Agency (BPN) for overlapping in the issuance of land certificates in order to address the existing legal issues. The research method used is normative research using a statutory approach and a conceptual approach. The results of this study indicate that recognition of customary rights of indigenous communities often faces challenges, particularly related to the unclear status of land ownership. The Nusantara Capital City (IKN) development project has further exacerbated this problem, as it has the potential to displace indigenous communities who have inhabited the area for a long time. To address this issue, there is a need for a more comprehensive effort to recognize and protect the rights of indigenous communities. This includes providing legal certainty for customary rights, actively involving indigenous communities in the decision-making process, and providing suitable replacement land for indigenous communities affected by development. In this way, the development of the IKN can be carried out without sacrificing the rights of indigenous communities and the principles of justice and sustainability.